Oncology Nurses’ Knowledge and Attitude towards Palliative Care - Thapa, Usha; Panthi, Sabita; Neupane, Laxmi (Nepalese Journal of Cancer, 2023)
Introduction:  Palliative care (PC) is considered an integral component of comprehensive cancer care. Insufficient knowledge among nurses was one of the main obstacles to providing high-quality palliative care services. This study assessed oncology nurses' knowledge and attitude toward palliative care.Method:   A cross-sectional study was conducted among 125 oncology nurses working at B.P. Koirala Memorial Cancer Hospital (BPKMCH). A simple random sampling technique was used. The self-administered questionnaire: Palliative Care Quiz for Nursing (PCQN) and “From melt Attitudes toward Care of the Dying Scale (FATCOD) were used to assess knowledge and attitude. The data were analyzed and interpreted using SPSS version 22. The p-value was set at